Measurement of defects in a plate using dry-coupled interdigital transducer–based scanning laser Doppler vibrometer. (March 2021) - Kang, To; Han, Seong-Jin; Moon, Seongin; Han, Soonwoo; Jeon, Jun Young; Park, Gyuhae
The interdigital transducer–based scanning laser Doppler vibrometer has recently been introduced to efficiently generate the symmetric mode for damage detection of shallow defects in thick plates. To measure shallow defects in a carbon steel plate, the excitation frequency is optimized based on the analysis of wavenumber sensitivity and degree of separation between modes. Even though the interdigital transducer–based scanning laser Doppler vibrometer method using continuous excitation is a promising method for visualizing defects in plate-like structures, the interdigital transducer has to be coupled to media, such as oil or water, to minimize the variation in acoustic impedance between the lead zirconium titanate and the plate-like structures. In this study, we develop a dry-coupled interdigital transducer–based scanning laser Doppler vibrometer system for the detection of shallow defects in a plate to facilitate easy mounting and demounting from the plate. To verify the proposed dry-coupled interdigital transducer–based scanning laser Doppler vibrometer, plates with four and eight different depth defects are introduced, and it is demonstrated that the defects in thick plates measured by dry-coupled interdigital transducer–based scanning laser Doppler vibrometer are visualized compared to those measured by interdigital transducer–based scanning laser Doppler vibrometer.